2022
DOI: 10.3390/polym14204433
|View full text |Cite
|
Sign up to set email alerts
|

Study of a High-Temperature and High-Density Water-Based Drilling Fluid System Based on Non-sulfonated Plant Polymers

Abstract: The environment-friendly water-based drilling fluid system developed for the petroleum development industry cannot successfully withstand temperatures up to 180 °C, and most high temperature-resistant additives with sulfonic acid groups that have been successfully applied to water-based drilling fluid are not good for environmental protection. In order to solve the above technical problems, a non-sulfonated filtrate reducer and viscosity reducer with resistance to high temperature were prepared by using humic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
1
0
1
Order By: Relevance
“…synthesized the nonsulfonated filtrate reducer with resistance to high temperature using a three‐step procedure consisting of polycondensation reaction among humic acid, lignin and formaldehyde, free radical polymerization of acrylic acid (AA), acrylamide (AM), N ‐vinylpyrrolidone (NVP) and N ‐(3‐triethoxymethiloxanyl) propyl acrylamide (APTS) in aqueous solution and an amidation reaction by mono‐ethanolamine. [ 89 ] The obtained copolymers have a very high thermal stability, thus exhibiting good high‐temperature resistance. The copolymers were used to prepare high‐performance water‐based drilling fluids and the API filtration loss with 3.0 wt% nonsulfonated copolymer as filtrate reducer was only 6.2 mL, which indicated that it had an excellent performance in filtration loss after aging at high temperature.…”
Section: Natural Polymers and Their Derivatives As Filtrate Reducersmentioning
confidence: 99%
“…synthesized the nonsulfonated filtrate reducer with resistance to high temperature using a three‐step procedure consisting of polycondensation reaction among humic acid, lignin and formaldehyde, free radical polymerization of acrylic acid (AA), acrylamide (AM), N ‐vinylpyrrolidone (NVP) and N ‐(3‐triethoxymethiloxanyl) propyl acrylamide (APTS) in aqueous solution and an amidation reaction by mono‐ethanolamine. [ 89 ] The obtained copolymers have a very high thermal stability, thus exhibiting good high‐temperature resistance. The copolymers were used to prepare high‐performance water‐based drilling fluids and the API filtration loss with 3.0 wt% nonsulfonated copolymer as filtrate reducer was only 6.2 mL, which indicated that it had an excellent performance in filtration loss after aging at high temperature.…”
Section: Natural Polymers and Their Derivatives As Filtrate Reducersmentioning
confidence: 99%
“…在pH为9~11的水基钻井液中, 溶解的氢氧化铝和腐植酸絮凝物能迅速沉淀出来, 有 效地堵塞和密封页岩裂缝. Xu等 [114] 以腐植酸、木质 素和多功能单体为原料, 制备了一种非磺化降滤失剂 FLO-H和耐高温降黏剂VR-H. 研究结果表明, 有FLO-H和VR-H的水基钻井液在200℃的高温下具有优异的 稳定性和滤失性, 满足高温深井钻井的要求.…”
Section: 改善土壤的物理(土壤孔隙度、体积密度和持水量)、 化学(Ph、电导率、营养元素)和生物(微生物量和矿 化或降解程度)参数...unclassified